1031 A Mixed Methods Feasibility Study of Extracorporeal Shockwave Therapy for Diabetic Foot Ulcers. (12th October 2021) - Hitchman, L; Totty, J; Lathan, R; Sidapra, M; Smith, G; Carradice, D; Chetter, I
Abstract: Aim: The purpose of this mixed methods feasibility study was to assess the feasibility of delivering ESWT to patients with DFUs. It also aimed to explore any potential clinical effect of ESWT on wound healing and investigate whether ESWT may offer any patient reported benefits. Method: A single centre mixed methods feasibility study. Patients with a DFU who met the eligibility criteria underwent ESWT 3 times in over 7 days. Primary outcome was feasibility of delivering the intervention. Secondary outcomes included wound size, number of DFU healed at 12 weeks and quality of life. Semi-structured interviews explored participants experience of undergoing ESWT. Results: 22.6% (24/106) of patients screened were recruited. The mean attendance to clinic was 90.9% and 65.1% to follow up. The mean score for acceptability and tolerability was 9.86 (SD 0.48, 95% CI 9.62-10.01) and 9.15 (SD 2.57, 95% CI 7.87-10.42) respectively. There were no serious adverse events or side effects. 45.5% of DFU healed during follow up and quality of life scores improved until 8 weeks. Key themes identified from the qualitative interviews were desire for the fast healing, improved quality of life, new treatments must be flexible and accessible on transport. Conclusions: This study has shown it is possible to recruit and retain patents into this research. This study supports development of a large randomised control trial to determine the clinical and cost effectiveness of ESWT for DFU healing.